2010
DOI: 10.1007/s00408-010-9243-6
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein A Stimulates Release of Neutrophil Chemotactic Factors by Alveolar Type II Pneumocytes

Abstract: Mucosal immunity is an important mechanism in the response to injury. Our hypothesis is that surfactant protein A (SP-A) is an autocrine factor that stimulates alveolar type II epithelial cell release of neutrophil chemotactic factors by binding to the SP-A receptor expressed by these cells. We examined (1) the effect of SP-A (20 μg/ml) or IL-1β (10 ng/ml) on release of neutrophil chemotactic factors by primary cultures of type II cells or alveolar macrophages, and (2) the effect of intratracheal instillation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…However, the mechanism through which trachea gets colonized with bacteria in CPAP‐supported infants is unclear and has never been investigated, simply because of the lack of knowledge about its existence. Surfactant plays a function in the immune system of the respiratory system 19,20 . The exposure of lower respiratory tract and alveoli to oxygen may induce a bio‐trauma that ameliorates the integrity of the endothelial and epithelial cell‐lining, making them incompetent in preventing bacterial residence 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism through which trachea gets colonized with bacteria in CPAP‐supported infants is unclear and has never been investigated, simply because of the lack of knowledge about its existence. Surfactant plays a function in the immune system of the respiratory system 19,20 . The exposure of lower respiratory tract and alveoli to oxygen may induce a bio‐trauma that ameliorates the integrity of the endothelial and epithelial cell‐lining, making them incompetent in preventing bacterial residence 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Surfactant plays a function in the immune system of the respiratory system. 19,20 The exposure of lower respiratory tract and alveoli to oxygen may induce a bio-trauma that ameliorates the integrity of the endothelial and epithelial cell-lining, making them incompetent in preventing bacterial residence. 21 Another factor could be related to some limitation in the motility of premature infants while attached to the CPAP device.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous studies have shown that SP-A stimulates the chemotactic activity of alveolar neutrophils 11 and myeloperoxidase activity is increased in hepatopulmonary syndrome in rats 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary surfactant, which is secreted by alveolar type II pneumocytes, reduces surface tension at the air/liquid interface of the alveoli and stabilizes alveoli at low lung volumes [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…SLPI prevents degradation of matrix metalloproteinase, a molecule involved in antigen apoptosis through the proteolytic breakdown of extracellular matrix components. Release of neutrophil chemotactic factors by alveolar type II pneumocytes is also regulated by SP-A [21]. Studies on animal models with SP-A and -D deficiencies have sought to confirm these findings.…”
Section: Biochemical Background Of Surfactant Analoguesmentioning
confidence: 99%